Enhanced Methanol Electrooxidation Performance Based on Pt Cluster‐Decorated CuCoO2 on Carbon. Issue 28 (26th July 2022) - Xing, Wanpei; Kong, Lingwei; Zhang, Xulei; Zhang, Yan; Tu, Xi; Yu, Jia; Yang, Jianhua; Zhou, Chao; Zhu, Wenhuan; Huang, Jun
Abstract: Nowadays, the high cost and poor durability of commercial catalyst Pt/C for methanol oxidation reaction have impeded the further development of direct methanol fuel cells. Herein, we firstly introduced a delafossite CuCoO2 to act as the support of noble metal Pt. The strong metal support interaction between Pt and CuCoO2, abundant hydroxide species and active sites on the surface of catalyst may be the key factors for enhanced performances of methanol oxidation. Pt‐CuCoO2 /C achieved a mass activity of 1.16 A mgPt −1, which obtained 3.02 times enhancement compared with commercial Pt/C (0.38 A mgPt −1 ). The If /Ib value of Pt‐CuCoO2 /C is 1.96, much higher than that of Pt/C (0.76), demonstrating favorable anti‐poisoning ability. After 200 times cycling, Pt‐CuCoO2 /C still maintained 77.1 % of its initial activity, exhibiting superior COads intermediate tolerance and stability. Low cost, better performances and stability of Pt‐CuCoO2 /C reveal that it can be seen as a hopeful catalyst. Abstract : Using quasi‐hexagonal delafossite‐structure CuCoO2 plates incorporated Vulcan carbon XC‐72R as the support of Pt catalyst can achieve superior catalytic activity, apparent anti‐poisoning ability and good stability with low cost for methanol oxidation reaction. The hydroxide species absorbed on the surface of CuCoO2 plates react with COads intermediates, recovering the active sites on Pt and accelerating the methanol oxidation process.